Between Atlantic and Mediterranean: Changes in technology during the Late Glacial in Western Europe and the climate hypothesis. (15th January 2017) - Naudinot, Nicolas; Tomasso, Antonin; Messager, Erwan; Finsinger, Walter; Ruffaldi, Pascale; Langlais, Mathieu
Abstract: During the second half of the Upper Paleolithic, Europe seems to have been divided in two vast techno-cultural entities with their particular chronological sequence: the Western Europe "classical sequence" and the Epigravettian sequence in the South. Essentially because of an imbalance of data and differences in methodologies between these two regions, their Upper Paleolithic sequences have rarely been compared. Thanks to the development of lithic technology in Europe and a recent active research about the Late-Glacial, it is today possible to attempt such a challenging exercise of comparing these two long sequences. In this paper, we solely focus on the Late Glacial. If the rare existing attempts of comparison focused on typology of lithic assemblages, our paper aims for a more global approach of lithic industries, based on recent technological studies. This approach allows highlighting key elements in term of human behaviors. Our data suggest a similar process of change between Western Europe and the Epigravettian during GI-1 (Bølling–Allerød). All the criteria of the so called "azilianization process" are actually present in the Epigravettian evolution sequence. This similar trend within both evolution sequences stopped abruptly, during the GS-1 (Younger Dryas). During this period and the very beginning of the Holocene (Preboreal), a massive return of blades and bladelets with high qualitative standards occurred in Western Europe while the simplification process is still in course in the Epigravettian region. In this paper, we attempt to compare the various responses of vegetation to the major climatic instability of the Late Glacial across Europe using a critical survey of the available environmental data. Considering the boundary that could have represented the Alps between Epigravettian and the Western Europe sequence, two high-resolution environmental sequences from north and south of the Alps are especially examined. Are the differences in terms of environmental changes between these two areas significant? Did they play a role in human behaviors and motivate technological changes? The comparison of palaeoenvironmental data with archaeological results tends to comfort some hypothesis of environmental determinism proposed by scholars, but also provide new elements moderating regional models that cannot really be applied at a continental scale. Climatic correlations with socioeconomic changes highlighted in this paper are no more than one possible way of investigation that will need to be tested and discussed in further research.